De Pont : de Collectie. - De Pont, Jos; Delfgaauw, Leo; Driessen, Hendrik; Heezen, Henriëtte; Lütticken, Sven; Pelsers, Lisette; Steevensz, Bert; Verge, Anouk La; van Asseldonk, Wilma; van den Boogerd, Dominic; van der Meulen, Sjoukje (Tilburg : Stichting De Pont, 1998)
Alberola, Jean-Michel ; Andriesse, Jan ; Asher, Dan ; Birza, Rob ; Boltanski, Christian ; van den Broeck, Frank ; Broek, Hans ; de Cordier, Thierry ; Daniels, René ; Dibbets, Jan ; Douglas, Stan ; Dumas, Marlene ; Frize, Bernard ; Geelen, Guido ; de Goede, Kees ; Heilmann, Mary ; van Hoek, Hans ; Horn, Roni ; Kapoor, Anish ; Laib, Wolfgang ; Long, Richard ; Männikkö, Esko ; Merz, Gerhard ; Mulders, Marc ; Oursler, Tony ; Penone, Giuseppe ; Polke, Sigmar ; Rainer, Arnulf ; Richter, Gerhard ; Schouten, Marien ; Schütte, Thomas ; Serra, Richard ; Trockel, Rosemarie ; Turrell, James ; Tuymans, Luc ; Verhoef, Toon ; Viola, Bill ; Visch, Henk ; van Vught, Reinoud ; Wall, Jeff ; Zakrzewski, W. Jan ; Zandvliet, Robert
Text Dutch-English
boek